A FORMAÇÃO PROFISSIONAL DOS TÉCNICOS DO NÍVEL MÉDIO NO CONTEXTO DA SOCIEDADE EM MUDANÇAS: desafios, limites e perspectivas do CEFET-UNEDI-MA. - Gomes, Marco Antônio Nogueira (2008)
It was with the technological revolution and acirramento international competition that the world of work began to undergo changes that pass, deeply, working conditions and life of the working class, reaching its direct representation of social agencies, as well as changes in process training that worker, imposing to education and, in particular, vocational training some demands and challenges. The overall purpose of the study is to examine the training of technical-level medium in society changes, seeking to seize the CEFET-UNEDI-MA can respond to the challenges of the world of work, with limits and prospects identified in the planning legal. Elected as specific objectives, the following: a) review the proposed guidelines and curriculum for the training of professional technicians from the average level, indicating trends in the planning and legal implications b) understand what brings the law, in fact, of substantially to the formation of the worker in society changes. The results demonstrate the limited autonomy of the school in working to design a curriculum that promotes the proper training to the context of society in change. As a corollary to this restriction, stand Guidelines and the Laws of Basic Education, together with their legal opinions that render a proposal for a training that meets the expectations of teachers and students.